Key components of chronic care management programs: qualitative descriptions of care managers’ practice - Izumi, Shigeko; Mood, Laura; Velk, Lace; Szper, Courtney; Fifield, Alexis; Ayala, Darcey; Dawson, Walter D.; Womack, Dana (BMC Health Services Research, 2025)
Increasing numbers of people live with chronic conditions. Yet, healthcare systems are often designed based on an acute care model that is not well-aligned with the needs of patients with chronic conditions, resulting in poor patient outcomes and high healthcare costs. To better assist patients living with chronic conditions, there is an urgent need to develop chronic care management models that are effective, scalable, and financially sustainable. The aim of this study was to identify and describe key components of chronic care management practice as a foundation to develop such a program.